A small‐molecule PAI‐1 inhibitor prevents bone loss by stimulating bone formation in a murine estrogen deficiency‐induced osteoporosis model. Issue 4 (16th February 2018) - Jin, Guangwen; Aobulikasimu, Alkebaier; Piao, Jinying; Aibibula, Zulipiya; Koga, Daisuke; Sato, Shingo; Ochi, Hiroki; Tsuji, Kunikazu; Nakabayashi, Tetsuo; Miyata, Toshio; Okawa, Atsushi; Asou, Yoshinori
Abstract : Osteoporosis is a progressive bone disease caused by an imbalance between bone resorption and formation. Recently, plasminogen activator inhibitor‐1 (PAI‐1) was shown to play an important role in bone metabolism using PAI‐1‐deficient mice. In this study, we evaluated the therapeutic benefits of novel, orally available small‐molecule PAI‐1 inhibitor (iPAI‐1) in an estrogen deficiency‐induced osteoporosis model. Eight‐week‐old C57BL/6J female mice were divided into three groups: a sham + vehicle (Sham), ovariectomy + vehicle (OVX + v), and OVX + iPAI‐1 (OVX + i) group. iPAI‐1 was administered orally each day for 6 weeks starting the day after the operation. Six weeks of iPAI‐1 treatment prevented OVX‐induced trabecular bone loss in both the femoral bone and lumbar spine. Bone formation activity was significantly higher in the OVX + i group than in the OVX + v and Sham groups. Unexpectedly, OVX‐induced osteoclastogenesis was partially, but significantly reduced. Fluorescence‐activated cell sorting analyses indicated that the number of bone marrow stromal cells was higher in the OVX + i group than that in the OVX + v group. A colony‐forming unit‐osteoblast assay indicated enhanced mineralized nodule formation activity in bone marrow cells isolated from iPAI‐1‐treated animals. Bone marrow ablation analysis indicated that the remodeled trabecular bone volume was significantly higher in the iPAI‐1‐treated group than that in the control group. In conclusion, our results suggest PAI‐1 blockade via a small‐molecule inhibitor is a new therapeutic approach for the anabolic treatment of postmenopausal osteoporosis. Abstract : Osteoporosis is a progressive bone disease caused by an imbalance between bone resorption and formation. In this study, we evaluated the therapeutic benefits of novel, orally available small‐molecule PAI‐1 inhibitor (iPAI‐1) in an estrogen deficiency‐induced model of osteoporosis. iPAI‐1 administration increased bone volume through enhancement of bone formation and suppression of bone resorption. iPAI‐1 represents a new therapeutic approach for the anabolic treatment of postmenopausal osteoporosis.